The Implications of Turkey's Polygamy Ban on Islamic Family Law - Nurjannah; Akbarizan; Munir, Akmal Abdul (JURNAL MERCATORIA, 2025)
This article aims to examine the rationale behind Turkey's ban on polygamy, the implications of the prohibition as well as the contradiction with Islamic family regulations. The study uses a qualitative methodology to examine the development of Turkish family law by applying both normative and historical approaches. The results show that the political and legal reforms carried out in 1926 under Mustafa Kemal Ataturk's rule are the source of Turkey's ban on polygamy and unfair treatment of women during the Ottoman Turkish era. Islamic law, which permits polygamy on reasonable grounds and limits it to four spouses, is in conflict with the ban on polygamy in Turki. The implications include the change of the principle marriage law to monogamy, the rise in illegal polygamy that leads to the disregard of the rights of wives and children, social deviations, changes in lifestyle, and injustice for couples who have certain conditions, like infertility or illness, that polygamy should be used to solution but are prohibited by the state.